Perma/culture
1 online resource (252 pages)
Keywords: In the face of what seems like a concerted effort to destroy the only planet that can sustain us, critique is an important tool. It is in this vein that most scholars have approached environmental crisis. While there are numerous texts that chronicle contemporary issues in environmental ills, there are relatively few that explore the possibilities and practices which work to avoid collapse and build alternatives.